ANALISIS STRATEGI PENJUALAN PRODUK IB HASANAH CARD MELALUI PROMOTION MIX DAN KESESUAIANNYA DALAM SISTEM EKONOMI ISLAM - Annisa Cahyani; Ahmad Sobari; Suyud Arif (Univ Ibn Khaldun Bogor, 2020)
In recent years, Islamic banking has experienced positive growth every year. Like this condition, conventional banks have faced new competitors. With the presence of sharia credit cards which are financing products iB Hasanah card products from BNI Syariah. The problem in this research is how the iB Hasanah card product sales strategy through the promotion mix and how it fits in the Islamic economic system at BNI Syariah Bogor Branch. The purpose of this study was to determine how the iB Hasanah card product sales strategy through the promotion mix and how it fits in the Islamic economic system at BNI Syariah Bogor Branch. The research method used in the preparation of this study uses descriptive qualitative methods using primary and secondary data, in addition to the data collection methods in this study using the method of observation, interviews, and documentation. Based on the research results of the iB Hasanah card product sales strategy conducted at BNI Syariah Bogor Branch using a strategy consisting of a promotion mix component with each element, namely advertising, sales promotion, publicity, personal selling, and direct marketing. Each element of the promotion mix is inseparable, interrelated. The promotion mix strategy has given strength to BNI Syariah Bogor Branch to compete in the world of Islamic financial institutions which are increasingly growing in competition. Results of the study, BNI Syariah strives to always apply the principles of sharia in running iB Hasanah card products. Based on these data, it is said that the iB Hasanah card product is in conformity with sharia principles that refer to Fatwa DSN No.54/DSN-MUI/X/2006 concerning sharia cards.